Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia - Bruce, Niel L.; Svavarsson, Jörundur (Zootaxa, 2018)
Three new species of Tridentella Richardson, 1905 are described from the New Caledonia region. All three species are smooth bodied or largely smooth bodied, and all were collected from the shelf around New Caledonia at depths from 150–760 metres. Tridentella palmata sp. nov. is characterised by pereopod 4 having numerous large robust setae on the carpus and an exceptionally long dactylus (7.0 times as long as proximal width); Tridentella katlae sp. nov. is the only species in the genus with medially united eyes that fill the head in dorsal view; Tridentella magna sp. nov. is the largest species in the genus (36 mm) and can be identified by the head having an anterior submarginal ridge and three submarginal tubercles on the poster margin. Tridentella takedai Nunomura 2006 (off Arasaki, Hokusuka-Shi, Kyushu, Japan) is formally transferred to Alcirona Hansen, 1905, forming Alcirona takedai (Nunomura, 2006) comb. nov.